Voros Coefficients at the Origin and at the Infinity of the Generalized Hypergeometric Differential Equations with a Large Parameter - Aoki, Takashi; Uchida, Shofu (Symmetry, Integrability and Geometry: Methods and Applications, 2022)
Voros coefficients of the generalized hypergeometric differential equations with a large parameter are defined, and their explicit forms are given for the origin and for infinity. It is shown that they are Borel summable in some specified regions in the space of parameters, and their Borel sums in the areas are given.